Exploring the perceived value of work as part of psychosocial rehabilitation of the state patient : Komani Hospital, Queenstown - Crocker, Ann Petro (Rhodes University, Faculty of Education, Centre for Social Development, 2002)
During the research an attempt was made to gain an understanding of the perceived value of work in psychosocial rehabilitation with the Sate patient at Komani Hospital. The respondents' motivation to work and what they gain from working, was investigated, as well as the experience of the nonworking respondents and their motivation not to work. To achieve this, ten respondents who were working and ten respondents who were not working, were interviewed. This study involves only a limited number of State patients at Komani Hospital and therefore findings cannot be generalised and also because the study was done at one Hospital only. A literature study was undertaken during which it was evident that work as part of vocational rehabilitation contributed to the well being of the mentally disabled person. It was also stated in the literature that the disabled person must be actively involved in his/her own rehabilitation planning and that the person must make conscious decisions to move away from the "sick" role and participate in his/her rehabilitation process. Interview schedules were developed. Response received from the twenty participants was analysed. The overall findings of the study showed that the majority of respondents who were working, were motivated by money. The fact that the respondents work from Hospital and therefore disrupt the Hospital routine, work with abled co-workers and feeling needed by the factory where they are employed. also emphasised the respondents' motivation to keep on working. The findings of the study with the non-working group showed that some respondents want to work, but there are not enough work opportunities available in and from Hospital. The non-working respondents are not interested in working at the occupational therapy department because the pay patients get for work done at the department is too little, and therefore they reject the work there. Some respondents do not want to work. whether work is available or not. The non-working group is largely dependent on staff and co-patients for an income, or tobacco. The predominant activity of the non-working group of respondents during the day, as well as that of the majority of the working group respondents during weekends was sleeping, talking to friends, and smoking. The research findings, conclusions and recommendations could contribute to a better understanding of patients and the value of work for the patient in a Psychiatric Hospital.
Keywords: Work -- Psychological aspects; Mentally ill -- Attitudes